Recht en krom. Corruptie, ongelijkheid en rechtsbescherming in de vroegmoderne Nederlanden - Egmond, F. (BMGN - Low Countries Historical Review, 2001)
Straight or crooked: Corruption, inequality and civil rights in the early modern NetherlandsWith the help of several case studies from the 16thj 17th and 18th centuries, this paper focuses on two key questions: how did the ordinary citizens of the Dutch Republic protect themselves against corruption and the misuse of power by law enforcement agents, public prosecutors and the courts?; and, whose interests were actually being served by the early modern criminal justice system? Or, put another way: whose order was being maintained, and who was excluded from it? It is argued that the absence of a critical tradition in Dutch historiography concerning these issues fits in with the continental perspective in which the rights of the state are emphasized rather than the rights of the individual, whereas in England the opposite seems to be the case: a critical historiographical tradition juxtaposed to a past in which civil rights were emphasized, together with resistance to the state and other bastions of power, rather than on state privileges.